Deletions of kappa chain constant region genes in mouse lambda chain-producing B cells involve intrachromosomal DNA recombinations similar to V-J joining. - Moore, M W (1985)
We isolated and characterized the germ-line counterpart of a DNA segment designated RS (for recombining sequence), that is frequently recombined in mouse lambda light chain-producing B lymphocytes. Using Southern blot analyses of myelomas and mouse-Chinese hamster fusion cell lines, we found that RS DNA sequences are located on mouse chromosome 6, evidently more than 15 kilobases downstream of the kappa light-chain locus. We find that a typical recognition site for Ig gene recombination is situated within germ-line RS sequences near the recombination points observed in at least two lambda chain-producing cell lines. This represents a complete and functional Ig recognition site that is not directly associated with Ig genes. We also characterized a recombined RS segment isolated from the cell line BM18-4.13.9. This recombined segment has a variable region kappa light chain gene (V kappa) joined directly to RS sequences. Our results suggest that the deletion of the kappa light chain constant region (C kappa) exon in many lambda chain-producing B cells is the result of RS recombination and that C kappa deletion may be mediated by the same processes as antibody gene V-J joining (J = joining segment gene). We discuss the potential biological significance of RS DNA recombination in B-cell maturation.